Split fertilization of phosphate in onion as strategy to improve the phopsphorus use efficiency - de Aquino, Rosiane Filomena Batista Almeida; Cavalcante, Adailza Guilherme [UNESP]; Clemente, Junia Maria; Macedo, Willian Rodrigues; Novais, Roberto Ferreira; de Aquino, Leonardo Angelo (Elsevier, 2021)
Phosphorus (P) is one of the nutrients applied in high amounts to vegetable crops due to high soil clays fixation. In view of the onion plant's limitations, the present study was formulated to access whether doses and forms of P splitting increase the efficiency of phosphate fertilization and influence physiological and growth characteristics of onion. Two experiments were carried out, one in a Red Yellow Latosol with a clay texture and the other in a Yellow Latosol with medium texture, both in a greenhouse. Evaluation was done on the interactions between two P doses and five split forms arranged in a factorial scheme (2 × 5) + 1 (control without P) in a completely randomized design and five replications. The agronomic efficiency, the recovery efficiency of P, the P-available in soil at the end of cultivation, the photosynthetic pigment content and the dry matter were positively influenced by P split, especially in clayey soil. Split application of P was strategic to reduce contact time of P with soil and prevent fixation guarantying greater nutrient availability in soil throughout the crop cycle. In medium-textured soil, the P movement became less problematic because of the lower P-fixing capacity, therefore low splitting effect.
Keywords: Allium cepa,Onion nutrition; Membrane stability; P fixation